Pengaruh Penggunaan Aplikasi RL2DIKTI dalam Meningkatkan Kemampuan Mahasiswa Program Studi Pendidikan Matematika dalam Melakukan Analisis Data Hasil Penelitian Skripsi - Rasmuin, Rasmuin; Azis, Azis; Umiyati, Iin Sri (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The formulation of the problem in this research was whether there was an influence of using the RL2DIKTI application in improving the ability of mathematics education study program student in analyzing data from thesis research result. The aim of the research was to find out that there is an influence of using the RL2DIKTI application in improving the ability of mathematics education study program student in analyzing data from thesis research result The research was quantitative research using pre experimental research desain. The population in this study were all student of the 6th semester mathematics education study program, totaling 36 people consisting of two classes. Because the population was less than 100%, the sample in this study was the same as the population. The data collection technique in this research used research instrument in the fronm of test, with data analysis technique using the mean difference test. Based on the research result, it was known that the ability of mathematics education study program student to analyze research data, in this case the average value the obtained befpre and after being treated based on the result of calculation using the mean defference the using the RL2DIKTI application, abtained a sig value. Amounting to 0.002<0.05, so H1 accepted. So it could be concluded that the RL2DIKTI application could improve the ability of education study program student in analyzing data from thesis research result.